Profile and Economic Impacts of Agriculture and Natural Resource Industries in the Northwest Region of Florida - Mohammad Rahmani; Alan W. Hodges; W. David Mulkey (EDIS, 2005)
This report provides a profile of agriculture and natural resource industries and an overview of their economic impacts for a 16-county region in northwest Florida (Figure 1). Additional reports provide similar information for the central, northeast, south, and Suwannee River Basin areas of the state. The report is based on data from the IMPLAN Pro database for Florida counties for 2002 and data from the 2002 Census of Agriculture.